Perancangan Video Dokumenter Sekarya Setara untuk Meningkatkan Disability Awareness di Bidang Seni - Muhammad Haidar; Gunawan Susilo (Jurnal Desain Komunikasi Visual, 2025)
This research aims to design the documentary video “Sekarya Setara” as a medium to increase public awareness regarding the importance of support for persons with disabilities in the arts. Employing a procedural design approach encompassing pre-production, production, and post-production phases, this study utilized data collected through observations, interviews, questionnaires, and documentation analyzed qualitatively. The findings reveal that emotional support, technical guidance, and adaptive learning environments are critical for the artistic development of individuals with disabilities, as demonstrated by the narrative of a deaf Remo dancer. Consequently, the resulting documentary, complemented by supporting media such as posters and merchandise, proves effective as an educational tool for inclusivity. In conclusion, “Sekarya Setara” serves as a impactful instrument for disability awareness campaigns and establishes a viable model for inclusive-oriented media production within the arts sector.